Tradisi Lisan Naskah Bekesah Puspakrama (Tinjauan Semiotik) - Ahmad Turmudzi (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2020)
This study aims to gain an in-depth understanding of the meaning of cultural symbols contained in the Pusakrama Manuscript. Manuscript which relates to moral and spiritual concepts. This research is a qualitative semiotic approach with content analysis techniques. As for the results of this study, there are 30 songs (paragraphs) that have cultural significance in the Sasak community, consisting of; 1) Trust in God (Apage) as much as 5 data, 2) Love for spouse (Eros) consists of 3 data, 3). Love for others (philia) consists of 9 data, 4). Self-love (Narcissistic) consists of 2 data, 5). Care for the environment (Cosmic) consists of 3 data, and 6). Love for the country (Patriotic) consists of 4 data. Bekesah Puspakrama is an oral taradisi script used in various traditional ritual activities. The implication of this research is expected to have an impact on the development of language and literary education as well as efforts to preserve oral tradition texts in Indonesia.